DAMPAK PENERAPAN UNSUR POLITIK DALAM PENILAIAN KINERJA TERHADAP KEPUASAN KERJA DAN KEINGINAN UNTUK BERHENTI BEKERJA Studi pada dosen-dosen tetap non-PNS sekolah tinggi di Banjarmasin - Arief Noviarakhman Zagladi (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2020)
The politics of performance appraisal has a role in determining the accuracy of the performance appraisal and this can cause problems in organizations. This study aims to determine whether the politics of performance appraisal have an impact on job satisfaction and will ultimately have an impact on the turnover intention. The research was conducted on permanent non-civil servant lecturers in graduate school in Banjarmasin, South Kalimantan. The sample used was 56 lecturers. The results of the analysis using path analysis found that motivational reasons in performance appraisal politics did not have a significant effect on job satisfaction and the desire to stop working, while punishment reasons in performance appraisal politics had a significant effect on job satisfaction and the desire to stop working.